2018
DOI: 10.1186/s41983-018-0036-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25(OH) vitamin D level and its relation to diabetic peripheral neuropathy in Egyptian patients with type 2 diabetes mellitus

Abstract: BackgroundSome clinical studies demonstrated a significant association between vitamin D deficiency and diabetic peripheral neuropathy (DPN).ObjectiveThis study aims to evaluate the correlation between serum levels of 25(OH) vitamin D and DPN in Egyptian patients with type 2 diabetes mellitus (T2DM).Patients and methodSixty patients were known to have T2DM, which classified into the following: group I included 40 patients with DPN and group II included 20 diabetic patients, without DPN, compared with 30 appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 47 publications
6
26
1
Order By: Relevance
“…In studies conducted, Vitamin D levels are observed to be low in DM patients (14,28). Studies showed that Vitamin D deficiency has an effect and an important role in the development and severity of DPN (1,14). In our study, 25 (OH) vitamin D serum levels were significantly lower in patients with PNP than in patients without PNP.…”
Section: Resultssupporting
confidence: 41%
See 2 more Smart Citations
“…In studies conducted, Vitamin D levels are observed to be low in DM patients (14,28). Studies showed that Vitamin D deficiency has an effect and an important role in the development and severity of DPN (1,14). In our study, 25 (OH) vitamin D serum levels were significantly lower in patients with PNP than in patients without PNP.…”
Section: Resultssupporting
confidence: 41%
“…In studies conducted, Vitamin D levels are observed to be low in DM patients (14,28). Studies showed that Vitamin D deficiency has an effect and an important role in the development and severity of DPN (1,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the association of vitamin D level with diabetic neuropathy, a recent meta-analysis has shown that vitamin D deficiency could be associated with the development of diabetic neuropathy in Caucasian patients with type 2 DM 13. A number of other studies conducted on different populations have also shown an association between the levels of serum vitamin D and diabetic neuropathy 12 25–27…”
Section: Introductionmentioning
confidence: 99%
“…Abdelsadek et al, 25 also found significant correlations between vitamin 25(OH)D level and amplitudes of motor peroneal, sensory median, and sensory sural nerves and the NCV of the sensory sural nerves ( p < 0.001). Lower levels of vitamin 25(OH)D were associated with a decrease in NCV of peroneal and sural nerves.…”
Section: Discussionmentioning
confidence: 87%